Financial Record-Keeping Practices and Literacy of Ikat Weaving Msmes in Kupang City: Challenges and Opportunities - Bibiana, Rere Paulina; Luju, Elisabet; Juru, Paulus; Masri, Marius (Universitas Muhammadiyah Sorong, 2025)
This research aims to analyze the level of financial literacy, record-keeping practices, challenges, and opportunities for developing ikat weaving MSMEs in Kupang City. A quantitative approach was employed using a survey method with 60 MSMEs, and data analysis was conducted through Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that the level of financial literacy of MSMEs is moderate (58.2%), with recording practices that are still simple and not yet digitized. The main challenges faced include a limited understanding of accounting, time constraints, and inadequate technological skills. However, there is a significant opportunity to improve the quality of recording through training, the adoption of digital applications, and support from various stakeholders. Inferentially, financial literacy and recording practices have a positive and significant impact on MSME development opportunities, whereas challenges have a significant negative impact. These findings highlight the importance of synergy among the government, financial institutions, academics, and communities in enhancing the financial reporting capacity of MSMEs, tailored to local culture, to support business sustainability and the achievement of sustainable development goals.